WOMEN LEADERSHIP COMPETENCY FROM THE PERSPECTIVE AMONG LECTURER AT UNIVERSITY XYZ - Fadillah Ismail, Teh Hui Chin, Adibah Abdul Kadir, Adnan Ali Hasan al Hosaini (International Journal of Advanced Science and Technology, 2020)
In an increasingly competitive and changing environment, women leaders in education face a variety of challenges. Although women dominate the labor force in large number, however in higher education sector, most of senior lecturers are men. The purpose of this study is to examine the leadership competency of women lecturer in the perspective of a lecturer at University XYZ and the effect of gender in ranking of competency skill. This study also intended to know the role of ranking in advancing women to a senior lecturer positions. This quantitative study used simple random sampling technique with 361 lecturers of University XYZ as the sample of the study. Questionnaire was distributed through online. The data was then analyzed by using Statistical Package for Social Science v22 (SPSS version 22). The results shows that self-management are the most important leadership competencies needed by women lecturers, follow by communication, business acumen, and leadership ability. Leadership competency is needed for the career development especially for women leaders in education. The model of leadership competency is a guideline for a women leader to evaluate their leadership competency in education sector.